Strategi Keterampilan Kepemimpinan Kepala Sekolah - Luqmanul Hakim; Samiyah (CV Putra Publisher, 2024)
Effective leadership plays a central role in the success of an institution, including in educational institutions. Leaders, especially principals, are expected to have the ability to guide all elements of the organization to achieve the desired goals effectively and efficiently. This study aims to describe and analyze the development of principal leadership skills, focusing on three main skills, namely interpersonal skills, trust-building skills, and decision-making skills. The methods used are literature review and descriptive analysis. The results of the study indicate that principals who have good leadership skills are able to create a harmonious educational environment, increase collaboration between members, and make strategic decisions that support the progress of the institution. Thus, strong leadership skills are needed to face the challenges in the world of education, as well as encourage the success of the institution in achieving its goals.